Trapping or tethering stones (TS): A multifunctional device in the Pastoral Neolithic of the Sahara. - Marina Gallinaro (PLoS ONE, 2018)
The Pierres de Ben Barour, also known as trapping or tethering stones (TS), are stone artefacts with notches or grooves usually interpreted as hunting devices on the basis of rock art engravings. Though their presence is a peculiar feature of desert landscapes from the Sahara to the Arabian Peninsula, we know little about their age, context and function. Here we present a new approach to the study of these artefacts based on a large dataset (837 items) recorded in the Messak plateau (SW Libya). A statistically-based geoarchaeological survey carried out between 2007 and 2011 in Libya, alongside landscape and intra-site analyses of specific archaeological features (such as rock art, settlement and ceremonial contexts), reveal that these artefacts were used for a prolonged period, probably from the early Holocene. This was followed by a multifunctional use of these devices, particularly during the Pastoral Neolithic phase (ca. 6400-3000 cal BC), with the highest concentrations being found near ceremonial contexts related to cattle burials.